Power imbalances, social inequalities and gender roles as barriers to true participation in national park management: The case of Korup National Park, Cameroon - Nchanji, Yvonne Kiki; Ramcilovic-Suominen, Sabaheta; Kotilainen, Juha (Elsevier, 2021)
Forest resource management has undergone profound changes in the last decades, including a tendency to apply participatory approach that seeks to involve local communities. However, the success of the participatory approach tends to remain dependent on the historical and societal context in question. To understand how the participation of forest communities has been changing as a result of the enforcement or non-enforcement of forest management practices, we carried out a study in Cameroon's Korup National Park, with villages within and outside the park that continue to utilise the resources in the park. The empirical research included focus group discussions and semi-structured interviews in three communities and key informant interviews with selected community members, government officials, and non-governmental organisations involved in the park's management. Research findings show that although the forest management system has changed in various policy documents, over the past years from a top-down to participatory approach, a centralised state system is still operational in the national park, with participatory approaches used merely as a legitimizing tool. We show how the existing horizontal power relations (such as gender roles within the communities) and vertical power relations (such as government-community dimensions) simultaneously impact the outcomes of participatory approaches on the ground. Finally, our case shows how the existing governance structures continue to reproduce inequalities and exclusions that originated from the colonial times and through path dependency still influence livelihoods and day-to-day survival of people in the communities.
Keywords: Forest communities; Power relations; participation; Korup National Park; Gender; Cameroon; Forest communities; Power relations; participation; Korup National Park; Gender; Cameroon